The Kaliningrad Question in the National Security of the Russian Federation - Elterişhan Elçibey (Avrasya İncelemeleri Dergisi)
In 1991, after the dissolution of the Soviet Union, the Kaliningrad region, which gained the status of an exclave, emerged as an important topic of discussion in Russian domestic and foreign policy discourse in the post-Soviet period and gained a strategic geopolitical importance. The region, which previously posed a threat to the West as the "military stronghold" of the Soviet Union, has been transformed into a Russian territory with reduced military elements in the post-Soviet period, primarily serving a defence function and having no direct connection with mainland Russia. The strategic importance of the region has been further enhanced by the successive eastward expansion of the European Union and NATO. Since the 1990s, Russia has strongly opposed the encirclement of Kaliningrad and the region has regained military importance under Vladimir Putin's leadership. As relations with the West deteriorated, Russia strengthened its military assets in the region and used it as a military staging ground against the West. As a result, Kaliningrad has become a security policy tool for the Kremlin and part of the ongoing threat to the Baltic states and Poland in particular. From Russia's perspective, Russian armed forces stationed in the region serve as a counterweight to an expanding NATO. Therefore, this article aims to analyse Russia's relations with the West through Kaliningrad from a military security perspective.